2020
DOI: 10.1177/2158244019898823
|View full text |Cite
|
Sign up to set email alerts
|

Informing iQOS Regulations in the United States: A Synthesis of What We Know

Abstract: The tobacco industry offers various products, including heated tobacco products (HTPs). Philip Morris International’s (PMI) “iQOS” has the greatest HTP market share, as well as research on its use and impact. iQOS was released in 2014 and is now in more than 40 countries. The U.S. Food and Drug Administration announced permission for PMI to sell iQOS in the United States in April 2019, and iQOS was launched in October 2019. Decisions pending its modified risk tobacco product (MRTP) application will occur subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
(108 reference statements)
1
17
0
Order By: Relevance
“…Several previously identified factors associated with support for tobacco control were documented with relation to cigarette smoke-free air policies, for example, being female, nonsmokers, or smokers who less frequently smoke and perceive quitting as more important [18]. However, fewer were found with relation to policies covering ENDS/HTPs, perhaps due to fewer people being aware of these products, the literature being less mature regarding their health risks, and limited public health campaigns communicating the risks of such products [1,8,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Several previously identified factors associated with support for tobacco control were documented with relation to cigarette smoke-free air policies, for example, being female, nonsmokers, or smokers who less frequently smoke and perceive quitting as more important [18]. However, fewer were found with relation to policies covering ENDS/HTPs, perhaps due to fewer people being aware of these products, the literature being less mature regarding their health risks, and limited public health campaigns communicating the risks of such products [1,8,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, prior research examining IQOS-related conversations on social media has been very limited. One study analyzed PMI marketing strategies and described a social media campaign in Israel that distributed positive promotional content related to IQOS [ 15 ]. Another study looked at IQOS influencer marketing on Instagram in Czech Republic and found that some Czech celebrities presented IQOS as part of aspirational and healthy lifestyle in their Instagram promotional posts [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…High exposure to HTP and cigarette advertising are consistent with the absence of a comprehensive advertising ban on tobacco products in Japan and evidence from other countries on exposure to tobacco advertising in unregulated channels. Pervasive global HTP marketing through prominent displays in convenience stores, duty-free stores, dedicated IQOS boutique stores, Internet and social media channels such as Instagram, Facebook, and Twitter and a spectrum of other youth-oriented events are well described in recent reviews [13,40,41]. Between 2017 and 2019, PMI reported a three-fold increase in the number of stand-alone IQOS stores worldwide from 63 to 199 and more than twice the number of retailers selling HTPs from 292 to 679 [42].…”
Section: Discussionmentioning
confidence: 99%